The analysis of the factor that causes fraudulent financial reporting with fraud diamond - Ni Komang Astri Yulistyawati; I Made Sadha Suardikha; I Putu Sudana (Jurnal Akuntansi dan Auditing Indonesia, 2019)
The purpose of this study is to obtain empirical evidence of the influence of the elements of fraud diamond namely: pressure, opportunity, rationalization, and capability on fraudulent financial reporting. The samples in the study were selected by usifigureng a non-probability sampling technique with a purposive sampling method with a total number of samples that met the sample selection criteria of 76 samples, namely 19 manufacturing companies during the four years of the 2011–2014 observation period. The collected data were analyzed by multiple linear regression analysis. Fraudulent financial reporting was measured using Dechow et al's F-Score (2007) which can be included as a first-pass test in evaluating the possibility of manipulation. This research showed that opportunity and rationalization are proven to be fraud diamond elements that most influence the occurrence of fraudulent financial reporting in the companies. While pressure and capability have no effect on fraudulent financial reporting. The implication of this study is that the ratio of total inventory as a proxy for opportunity measurement and the ratio of total accrual to total assets as a proxy for measurement of rationalization has a significant effect on fraudulent financial reporting, meaning that these ratios can be used by management to detect fraudulent financial reporting practices in manufacturing companies.